Metaphor Found in Coldplay’s Selected Song Lyrics - Hanif Wahyuda (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This research aims to identify the types of metaphor found in Coldplay’s selected songs. This is descriptive qualitative research. The lyrics used in this research were Coldplay’s selected song lyrics. There were 45 collected data from the lyrics. Structural metaphor appears 31 times, orientational metaphor appears 8 times, and ontological metaphor appears 6 times. Based on the research findings, it can be concluded that structural metaphor is the dominant type of metaphor that the song writer used to write the lyrics. It is suggested that next researchers who are interested in metaphor need to deepen the analysis because the use of unique choice of word and changing through times will provide new results.